Phenolic composition of four sage species: salvia farinacea, salvia mexico, salvia greggii and salvia officinalis - Pereira, Olívia R. (2016)
Salvia species are used worldwide for medicine purposes. In general, these medicinal plants have high amounts of flavonoids and phenolic acids, that are thought to be closely related to their health properties [1,2]. In this work, the aerial parts of Salvia farinacea, Salvia mexico, Salvia greggii and Salvia officinalis were extracted with hot water [3]. Extracts were evaluated for their total phenolic content by an adaptation of the Folin-Ciocalteu method and further analysed by high performance liquid chromatography associated with electrospray mass spectrometry (HPLC-DAD-ESI-MSn) in the negative ion mode [4], in order to identify their individual phenolic constituents. The aqueous extracts of S. farinacea, S. mexico, S. officinalis and S. greggii contained, respectively, 106±13, 159±38, 175±46 and 136±1 μg GAE/mg of total phenolics. These four species were characterized by a clear prevalence of caffeic acid derivatives, in particular of rosmarinic acid (MW 360), that is generally the most abundant phenolic compound in Salvia species [2,3]. In addition, S. mexico and S. officinalis contained moderate amounts of salvianolic acid B (MW 718). Among these two, S. mexico was richer in O-caffeoylquinic acid (MW 354), while the latter presented high amounts of salvianolic acid K (MW 556) and moderate amounts of its structural isomer. All the extracts were enriched in flavones: S. farinacea and S. officinalis contained high amounts of luteolin-O-glucuronide while S. mexico contained luteolin-C-glucoside with respective characteristic mass spectrometry fragmentation pattern m/z at 461→285 and m/z at 447→357, 327. Similarly, S. greggii extract presented high content of luteolin-7-O-glucoside ([M-H]− at m/z 447→ 285) and luteolin-C-glucoside and moderate quantities of apigenin-C-hexoside ([M-H]− at m/z 431→341, 311). Further studies are being undertaken in order to understand the contribution of these phenolic constituents in the biological activities of Salvia plants.